The Influence of Discovery Learning Model Assisted by Multimedia Module on Students' Critical Thinking Skill - Hidayatullah, Zul; Theofiulus Gratiamus Gusemanto (Impulse: Journal of Research and Innovation in Physics Education, 2024)
Proficiency in critical thinking is a crucial attribute that students must possess to effectively navigate the advancements in science and technology in the contemporary era of the fourth industrial revolution. Nevertheless, children's critical thinking abilities remain relatively deficient, and receive minimal instruction. Multimedia modules reinforce a discovery learning approach, providing an alternate method for developing critical thinking abilities. This research aims to determine the influence of the multimedia-assisted discovery learning paradigm on the development of students' critical thinking abilities. The research used a quasi-experimental approach, specifically a pretest-posttest control group design. Purposive sampling served as the sampling approach, ensuring that the students in the two classes under comparison shared the same initial competencies. We divided the 68 students in the research sample into two classes: the experimental class and the control class. We assess students' critical thinking abilities by administering an essay examination that evaluates their performance on critical thinking benchmarks. The data analysis for this research employs the independent t-test and the N-gain test. The study reveals that the experimental class outperforms the control class in terms of students' critical thinking abilities. The t-test's statistical significance, with a p-value of 0.000 or less than 0.05, confirms that the multimedia module-assisted discovery learning model has a significant impact on students' critical thinking abilities about momentum and impulse materials. The N-gain analysis of pretest and posttest results for students in the experimental class indicates a moderate rise in the five critical thinking indicators. We can conduct further studies to adapt this learning strategy to different topics. However, it is crucial to recognize that the instructor must invest time and creativity in preparing this multimedia module.